Rediscovering Morality through the Concept of Childhood. Issue 13 (December 2013) - Burdick-Shepherd, Stephanie
This chapter looks at John Dewey's consideration of childhood as a platform from which to view the significance of childhood in moral life. It argues that the concept of childhood is integral to our thinking in the teaching and learning relationship. When we consider childhood from Dewey's platform, we see that childhood is relevant to society both because it is a source of continued renewal and growth for our society and because its plastic and imaginative grounding enables children and their childhoods to fundamentally change educational relationships.